The Efforts to Improve the Investigators’ Performance in the Disclosure of Cyber Fraud Criminals by Subnit I Cyber-Crime Criminal Reserse of West Jakarta Metro Police Resort - Joshua Oktavianus Siagian (Budapest International Research and Critics University, 2023)
This study analyzes the investigators’ performance in Subnit I Cyber Crime Criminal Reserse of West Jakarta Metro Police in the disclosure of cyber fraud crimes. During 2018 and 2020, the cyber fraud cases have been increased significantly. Consequentially, the optimal investigators’ performance in disclosing the crime is required in order to continue their duty as the protector of the community. The qualitative approach was used with the type of field study research. To analyze the performance of investigators, the performance theory, the law enforcement theory, the resource theory, and information technology theory, were used, along with some relevant Perkapolri and prevailing laws regulations. The results of the study show that the investigators' performance at the investigation and inquiry stage to uncover the cyber fraud crimes has not been optimal. West Jakarta Metro Police has been working to improve the investigators’ performance by implementing PPDLT, specific allocation, and smart policing, but the efforts have not been sufficient. Several factors that hinder the optimal efforts to improve the investigators’ performance are limited personnel, request to increase the budget that has not been approved, no specific methods have been implemented to resolve the stack of cases, and the unavailability of technical SOP. Thus, it is necessary to transform the training and education methods for the investigators to tackle cyber fraud, to reform and trim bureaucratic procedures, and to strengthen the synergy with various parties that can help the investigations and both internally and externally.